Aneruptive Fever Associated with Antibodies to Rickettsia helvetica in Europe and Thailand - Fournier, Pierre-Edouard (American Society for Microbiology, 2004)
We report that eight patients from France, Italy, and Thailand had serological evidence of Rickettsia helvetica infection. The infection presented as a mild disease in the warm season and was associated with fever, headache, and myalgia but not with a cutaneous rash. R. helvetica should be suspected in patients with unexplained fever, especially following a bite from an Ixodes sp. tick.